INNOVATIVE EQUIPMENT FOR FORMING WEAR-RESISTANT SURFACE ALLOYS ON THE PROCESSING DISK MILLS - FYODOROV S.V; URINOV N.F.; SHARIPOV J.O. (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper investigates the major points of the innovative equipment for forming wear-resistant surface alloys on the processing disk mills. In this case, research has been conducted both theoretically and practically. It concludes with outcomes and shortcomings as a whole.